2007
DOI: 10.1029/2006jb004714
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the remote triggering capabilities of large earthquakes using data from the ANZA Seismic Network catalog (southern California)

Abstract: [1] Various studies have examined remote earthquake triggering in geothermal areas, but few studies have investigated triggering in nongeothermal areas. We search the ANZA (southern California) network catalog for evidence of remote triggering. Using three statistical tests (binomial, Kolmogorov-Smirnov, and Wilcoxon rank sum), we determine the significance of the rates and timing of earthquakes in southern California following large teleseismic events. To validate our statistical tests, we identify 20 local m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…All distant earthquakes identified as triggers can be seen in Tables S4 and S5. We did not find any instances of distant earthquakes triggering microearthquakes near Parkfield, an observation similar to Kane et al [] who investigated remote triggering along the San Jacinto Fault in southern California. Figure shows a comparison of the triggered behaviors caused by the 11 March 2011 M w 9.0 Tohoku‐Oki earthquake, as recorded in Parkfield ( σ = 10 kPa), Long Valley ( σ = 10 kPa), Coso ( σ = 7 kPa), and Geysers ( σ = 9 kPa).…”
Section: Parkfield Segment Observationsmentioning
confidence: 98%
“…All distant earthquakes identified as triggers can be seen in Tables S4 and S5. We did not find any instances of distant earthquakes triggering microearthquakes near Parkfield, an observation similar to Kane et al [] who investigated remote triggering along the San Jacinto Fault in southern California. Figure shows a comparison of the triggered behaviors caused by the 11 March 2011 M w 9.0 Tohoku‐Oki earthquake, as recorded in Parkfield ( σ = 10 kPa), Long Valley ( σ = 10 kPa), Coso ( σ = 7 kPa), and Geysers ( σ = 9 kPa).…”
Section: Parkfield Segment Observationsmentioning
confidence: 98%
“…Others have required events at any distance to occur within a short time after the passage of seismic waves. For example, Moran et al (2004) used a 1 h limit and Kane et al (2007) a 2 day window to examine triggered earthquakes. Selva et al (2004) used more intricate space-time constraints corresponding to the evolution of stress in a model system.…”
Section: Triggered Eruption Of Mud Volcanoesmentioning
confidence: 99%
“…Brodsky and Prejean (2005) found that long-period (>30 s) waves are more effective at triggering earthquakes in the magmatically active Long Valley Caldera. However, Kane et al (2007) found that if there is a frequency dependence for triggered earthquakes in Southern California, the most effective frequencies must be >2 Hz.…”
Section: Frequency Dependence Of Observationsmentioning
confidence: 99%
“…Aftershock sequences are certainly the most easily observed pieces of evidence of such interaction. In spite of that clear empirical evidence, less clear and still under discussion are the physical mechanisms involved [ Felzer and Brodsky , 2006; Kane et al , 2007; Hill , 2008; Velasco et al , 2008; Richards‐Dinger et al , 2010]. In general, each earthquake can trigger (or inhibit) future earthquakes through different physical processes, such as dynamical triggering, coseismic and postseismic perturbations [e.g., Chéry et al , 2001; Marzocchi et al , 2003; Freed , 2005], pore fluids effects [ Keller and Loaiciga , 1993; Miller et al , 2004; Lombardi et al , 2010], etc., but the relative importance of each process, and how far in space and time such interactions may act, are still debated.…”
Section: Introductionmentioning
confidence: 99%